Emergence and Development of Wh-questions in Jordanian Arabic-speaking Children: A Longitudinal Study - Hamdan, Jihad; Hamdan, Hady (East European Journal of Psycholinguistics, 2020)
The main objective of this paper is to examine the emergence and development of wh-questions in two Jordanian Arabic-speaking pre-school children. Specifically, it investigates (1) how these children interact with wh-questions; which questions they find easier and thus earlier to acquire and why, and finally (2) what symptoms one can identify as characteristics of the intra-stage development of such questions. The data of the study are a subset of a large body of a longitudinal audio-taped corpus collected by the principal author, who happened to be a psycholinguist and the children’s grandparent, on the basis of three-day, weekly sessions over a period of five years. The recordings were made in the family home environment during routine activities, mainly after dinner, and mostly in the presence of family members. The findings reveal the acquisition of wh-questions is a complex process that supports a general cognitive maturity model interpretation. The acquisition of wh-questions that ask about concrete objects/entities, that is mi:n ‘who’, we:n ‘where’ and ʔe:ʃ/ʃu: ‘what’ are produced and developed at an earlier stage than those questions which ask about abstract objects/entities, that is le:ʃ ‘why’, ke:f ‘how’, ɡadde:ʃ/kam ‘how many/much’ and wakte:ʃ/ʔe:mta ‘when’. However, the subjects do not find the questions within each of the two sets equally easy/difficult. Put differently, in the first category, mi:n ranked first on the easy/difficult scale while ʔe:ʃ/ʃu: ranked third. Moreover, the order of acquisition in the second category suggested that it is easier for Jordanian Arabic-speaking children to ask about reason (le:ʃ-why) than about time (wakte:ʃ-when) and that to ask about quantity (ɡadde:ʃ/kam-how many/much) is more difficult than to ask about manner (ke:f-how). The study argues that the emergence of wh-words does not mark but the onset of an accumulative process which includes a host of symptoms on the way to adult-like acquisition.